Adaptations of Alteromonas sp. 76-1 to Polysaccharide Degradation: A CAZyme Plasmid for Ulvan Degradation and Two Alginolytic Systems - Koch, Hanna; Freese, Heike M.; Hahnke, Richard L.; Simon, Meinhard; Wietz, Matthias (Frontiers in Microbiology, 2019)
Studying the physiology and genomics of cultured hydrolytic bacteria is a valuable approach to decipher the biogeochemical cycling of marine polysaccharides, major nutrients derived from phytoplankton and macroalgae. We herein describe the profound potential of Alteromonas sp. 76-1, isolated from alginate-enriched seawater at the Patagonian continental shelf, to degrade the algal polysaccharides alginate and ulvan. Phylogenetic analyses indicated that strain 76 1 might represent a novel species, distinguished from its closest relative (A. naphthalenivorans) by adaptations to their contrasting habitats (productive open ocean vs. coastal sediments). Ecological distinction of 76-1 was particularly manifested in the abundance of carbohydrate-active enzymes (CAZymes), consistent with its isolation from alginate-enriched seawater and elevated abundance of a related OTU in the original microcosm. Strain 76-1 encodes multiple alginate lyases from families PL6, PL7, PL17 and PL18 largely contained in two polysaccharide utilization loci (PUL), which may facilitate the utilization of different alginate structures in nature. Notably, ulvan degradation relates to a 126 Kb plasmid dedicated to polysaccharide utilization, encoding several PL24 and PL25 ulvan lyases and monomer-processing genes. This extensive and versatile CAZyme repertoire allowed substantial growth on polysaccharides, showing comparable doubling times with alginate (2h) and ulvan (3h) in relation to glucose (3h). The finding of homologous ulvanolytic systems in distantly related Alteromonas spp. suggests CAZyme plasmids as effective vehicles for PUL transfer that mediate niche gain. Overall, the demonstrated CAZyme repertoire substantiates the role of Alteromonas in marine polysaccharide degradation and how PUL exchange influences the ecophysiology of this ubiquitous marine taxon.